Phase I/II Dose-Escalation Trial of 3-Fraction Stereotactic Radiosurgery for Resection Cavities From Large Brain Metastases: Health-related Quality of Life Outcomes. (November 2021) - Rahimy, Elham; Dudley, Sara A.; von Eyben, Rie; Pollom, Erqi L.; Seiger, Kira; Modlin, Leslie; Wynne, Jacob; Fujimoto, Dylann; Jacobs, Lisa R.; Chang, Steven D.; Gibbs, Iris C.; Hancock, Steven L.; et al.
Abstract : Objectives: We investigated differences in quality of life (QoL) in patients enrolled on a phase I/II dose-escalation study of 3-fraction resection cavity stereotactic radiosurgery (SRS) for large brain metastases. Methods: Eligible patients had 1 to 4 brain metastases, one of which was a resection cavity 4.2 to 33.5 cm 3 . European Organization for Research and Treatment of Cancer (EORTC) quality of life questionnaires core-30 (QLQ-30) and brain cancer specific module (QLQ-BN20) were obtained before SRS and at each follow-up. Nine scales were analyzed (global health status; physical, social, and emotional functioning; motor dysfunction, communication deficit, fatigue, insomnia, and future uncertainty). QoL was assessed with mixed effects models. Differences ≥10 points with q -value (adjusted P -value to account for multiplicity of testing) <0.10 were considered significant. Results: Between 2009 and 2014, 50 enrolled patients completed 277 QoL questionnaires. Median questionnaire follow-up was 11.8 months. After SRS, insomnia demonstrated significant improvement ( q =0.032, −17.7 points at 15 mo post-SRS), and future uncertainty demonstrated significant worsening ( q =0.018, +9.9 points at 15 mo post-SRS). Following intracranial progression and salvage SRS, there were no significant QoL changes. The impact of salvage whole brain radiotherapy could not be assessed because of limited data (n=4 patients). In the 28% of patients that had adverse radiation effect, QoL had significant worsening in 3 metrics (physical functioning, q =0.024, emotional functioning q =0.001, and future uncertainty, q =0.004). Conclusions: For patients treated with 3-fraction SRS for large brain metastasis cavities, 8 of 9 QoL metrics were unchanged or improved after initial SRS. Intracranial tumor progression and salvage SRS did not impact QoL. Adverse radiation effect may be associated with at least short-term QoL impairments, but requires further investigation. Abstract : Supplemental Digital Content is available in the text.